Relevansi Etika Bisnis dalam Industri Jasa Kesehatan - Alois A Nugroho (Center for Philosophy and Ethics, 2010)
Keberhasilan yang pantas dicatat oleh ekonomi pasar adalahterbentuknya masyarakat pasar. Perkembangan cara hidup modern berjalanbersamaan dengan perkembangan ekonomi pasar dan kedua hal ini secaramenakjubkan menghancurkan tatanan sosial yang dibangun sejak awal. Para dokterprofessional yang memegang secara teguh dan disiplin Sumpah Hippocrates harusberhadapan dengan godaan ekonomi dan masyarakat pasar. Dengan kata laindokter-dokter itu tidak lagi disiplin, jujur dan pengertian. Kini Sumpah Hippocrateshanya di atas kertas karena banyak dokter lebih memprioritaskan dimensiekonomis dari praktek kedokteran mereka dengan akibat ruang-ruang pengobatandan operasi yang seharusnya menjadi ruang personal berubah menjadi ruangfinansial belaka. The social and political upheavals that took place during the rise of the marketeconomy contends that the market and the modern social practice should be understood not asdiscrete elements, but as the single human making in the Market Society. The development of themodern way of life went hand in hand with the development of modern market economies and thatthese two were inevitably implied the destruction of the basic social order that had existedthroughout earlier history. Hippocratic medicine professionals that were notable for their strictprofessionalism, discipline, and rigorous practice became unsustainable to preserve their traditionalsystem of production and social order. The Hippocratic Oath that recommends physicians to bealways well-kempt, honest, calm, understanding, and serious are far removed from that of modernmedicine professionalism. The Today Hippocratic physician paid careful attention to the economicaspects of his practice rather than followed his detailed specifications given by Hippocratic Oathfor,